2009
DOI: 10.1093/schbul/sbp059
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia Is not Schizophrenia: Kraepelin's Error and the Need to Recognize Catatonia as an Independent Syndrome in Medical Nomenclature

Abstract: Catatonia is a motor dysregulation syndrome described by Karl Kahlbaum in 1874. He understood catatonia as a disease of its own. Others quickly recognized it among diverse disorders, but Emil Kraepelin made it a linchpin of his concept of dementia praecox. Eugen Bleuler endorsed this singular association. During the 20th century, catatonia has been considered a type of schizophrenia. In the 1970s, American authors identified catatonia in patients with mania and depression, as a toxic response, and in general m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(129 citation statements)
references
References 37 publications
(27 reference statements)
7
110
0
9
Order By: Relevance
“…Historically, catatonia has been classified as a subtype of schizophrenia but there is convincing evidence that catatonia is a syndrome that is not limited to patients with schizophrenia. 10,11 In our sample, only four out of the 25 subjects carried a diagnosis of schizophrenia. Moreover, improper treatment with antipsychotics can lead to clinical worsening and transition to lethal catatonia/neuroleptic malignant syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, catatonia has been classified as a subtype of schizophrenia but there is convincing evidence that catatonia is a syndrome that is not limited to patients with schizophrenia. 10,11 In our sample, only four out of the 25 subjects carried a diagnosis of schizophrenia. Moreover, improper treatment with antipsychotics can lead to clinical worsening and transition to lethal catatonia/neuroleptic malignant syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…42 Catatonia is common among chronically ill psychotic patients, but is more frequent in patients with mood disorders. [43][44][45] In pediatric populations, catatonia is reported among those with mental retardation and autistic spectrum disorder. 46,47 Recently, it was shown that most, if not all, patients with anti-N-methyl-D-aspartate-receptor encephalitis present with catatonic symptoms.…”
Section: Catatoniamentioning
confidence: 99%
“…Such an historical definition partially explains the lack of care regarding the catatonic syndrome and its dramatic underdiagnosis 10 . It has become clear, though, that catatonic symptoms can be observed not only in schizophrenia but also in several mental disorders, especially affective disorders 30,31 . Nowadays, many researchers consider since the term in the original language means ordinary.…”
Section: Discussionmentioning
confidence: 99%